Adult antisocial syndrome co‐morbid with borderline personality disorder is associated with severe conduct disorder, substance dependence and violent antisociality. (16th July 2012) - Freestone, Mark; Howard, Rick; Coid, Jeremy W.; Ullrich, Simone
ABSTRACT This study tested the hypothesis that syndromal adult antisocial behaviour (AABS) co‐morbid with borderline personality disorder (BPD) is a syndrome that emerges from severe conduct disorder (CD) in childhood and adolescence and is strongly associated, in adulthood, with both violence and substance dependence. In a sample of 8 580 community‐resident adults screened for the presence of personality disorders, the following predictions arising from this hypothesis were tested: first, that those with AABS co‐morbid with BPD would, in comparison with those showing AABS or BPD only, show a high level of antisocial outcomes, including violence; second, that adjusting for co‐morbid alcohol dependence would attenuate group differences in many of the antisocial outcomes, and violence in particular; and third, that the AABS/BPD group would show both a high prevalence and a high severity of CD, and that adjusting for co‐morbid CD would attenuate any association found between AABS/BPD co‐morbidity and violence. Results confirmed these predictions, suggesting that AABS/BPD co‐morbidity mediates the relationship between childhood CD and a predisposition to adult violence. The triad of AABS/BPD co‐morbidity, alcohol dependence and severe CD is likely associated with the risk of criminal recidivism in offenders with personality disorder following release into the community. Copyright © 2012 John Wiley & Sons, Ltd.